Association of psoriasis and alcoholism : osychodermatological issuel - Dediol, Iva (Array, 2009)
Psoriasis is a chronic, hereditary disease generally characterized by eruption of erythematous, silvery-scaled plaques, predominantly on the elbows, knees, scalp and trunk, affecting between 1-2% of the population worldwide. Psoriasis is a multifactorial disease of unknown etiology. It has been shown that in some patients alcohol abuse has been associated with psoriasis. Chronic alcohol abuse results in the impairment of health-related, social and occupational functioning. Therefore the association of psoriasis and alcoholism represents one of the major psychodermatological issues where a multidisciplinary approach (including dermatologist, psychiatrist, psychologist and others) is crucial for optimal outcome